Analisis Penggunaan CCTV Sebagai Alat Bukti Perspektif Hukum Positif Dan Hukum Islam - Cholqi Choirunnisa; Muhammad Saifuddin; Rahma Eka Fitriani; Wahyu Vina Nurrahma; Mahir Mahir (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Abstract: The use of CCTV as evidence in court is the result of technological advances. Furthermore, in criminal circumstances, CCTV footage can be used as solid evidence to prove someone's guilt. According to Islamic law, proof comes from the Arabic term al-Bayyinah, which means